The BCG replacement vaccine VPM1002: from drawing board to clinical trial. (May 2014) - Kaufmann, Stefan HE; Cotton, Mark F; Eisele, Bernd; Gengenbacher, Martin; Grode, Leander; Hesseling, Anneke C; Walzl, Gerhard
<x xml:space="preserve">Abstract</x> Tuberculosis remains a major health threat and vaccines better than bacillus Calmette-Guérin (BCG) are urgently required. Here we describe our experience with a recombinant BCG expressing listeriolysin and deficient in urease. This potential replacement vaccine has demonstrated superior efficacy and safety over BCG in Mycobacterium tuberculosis aerosol-challenged mice and was safe in numerous animal models including immune-deficient mice, guinea pigs, rabbits and nonhuman primates. Phase I clinical trials in adults in Germany and South Africa have proven safety and a current Phase IIa trial is under way to assess immunogenicity and safety in its target population, newborns in a high tuberculosis incidence setting, with promising early results. Second-generation candidates are being developed to improve safety and efficacy.